Neighborhood Decline and the Economic Crisis - Merle Zwiers; Gideon Bolt; Maarten van Ham; Ronald van Kempen (Institute for the Study of Labor (IZA), 2014)
Neighborhood decline is a complex and multidimensional process. National and regional variation in economic and political structures (including variety in national welfare state arrangements), combined with differences in neighborhood history, development and population composition, makes it extremely difficult to identify a unilateral process of neighborhood decline over time. Some scholars have tried to develop all-encompassing models to explain neighborhood decline; others have studied more deeply the relevance of a limited number of factors and developments in processes of decline. The literature has paid little attention to the influence of economic development on neighborhood development, and surprisingly, few studies have focused on the effects of the economic crisis on urban neighborhoods. The recent global economic and financial crisis affected many European and North-American cities in terms of growing unemployment levels and rising poverty in concentrated areas. At the same time, urban investments such as urban restructuring and neighborhood improvement programs have decreased, or come to a halt altogether. By reviewing existing literature, this paper aims to contribute to an understanding of neighborhood decline in light of the economic crisis. By formulating ten hypotheses about the ways in which the economic crisis might interact with processes of neighborhood decline, this paper aims to push the debate on neighborhood decline forward and calls for more contextualized research on neighborhood change. We will highlight challenges for future research and point to factors that need to be taken into consideration in a post-crisis society.
Keywords: I32; I38; O18; R23; 330; neighborhood decline; economic crisis; neighborhood regeneration; policy; housing market